EFEKTIFITAS MEDIASI PADA PENYELESAIAN SENGKETA HARTA WARISAN DI PENGADILAN AGAMA PAYAKUMBUH - Diana Eka Putri; Nuzul Rahmayani; Mahlil Adriaman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The settlement of inheritance disputes at the Payakumbuh Religious Court is a complex and sensitive matter, involving parties who have interests and family relationships. In an effort to overcome this problem, mediation is an effective alternative in finding a fair solution for all parties involved. This research aims to evaluate the effectiveness of mediation as an alternative method in resolving inheritance property disputes at the Payakumbuh Religious Court. The research method used is a field study with in-depth interviews with the parties involved in the inheritance dispute, the mediator, and the judge handling the case. The results showed that mediation had a positive impact on the settlement of inheritance disputes. The mediation process allows the disputing parties to communicate openly and seek mutual agreement. In addition, mediation also reduces the workload of the Payakumbuh Religious Court because some cases can be resolved persuasively through mediation without involving lengthy court proceedings.The effectiveness of mediation is also faced with several challenges, such as the refusal of some parties to mediate, differences in cultural approaches, and the tendency of some parties to insist on their demands. Therefore, more intensive efforts are needed to increase public understanding of the benefits of mediation in property dispute resolution.